Book Reviews. Issue 1 (1st January 2018) - Marrone, Gaetana; Anatrone, Sole; Heim, Julia; Benci, Jacopo; Koven, Mikel J.; Tabanelli, Roberta
Il giovane Fellini nello splendente fulgore della vita, Enzo Lavagnini (2011) Roma: Palombi Editori, 191 pp., ISBN: 9788860603944, p/bk, €15.00Destination Italy: Representing Migration in Contemporary Media and Narrative, Emma Bond, Guido Bonsaver and Federico Faloppa (eds) (2015) (Italian Modernities; vol. 21), Oxford, Bern, Berlin, Bruxelles, Frankfurt am Main, New York and Wien: Peter Lang, 467 pp., ISBN: 9783035395136, p/bk, 72.95A Very Seductive Body Politic: Silvio Berlusconi in Cinema, Nicoletta Marini-Maio (2015) Italy: Mimesis International, 118 pp., ISBN: 9788857526683, p/bk, 14.00Rewind Italia: Early Video Art in Italy/I primi anni della videoarte in Italia, Laura Leuzzi and Stephen Partridge (eds) (2016) New Barnet, Herts: John Libbey Publishing, 350 pp., ISBN: 9780861967216, h/bk, £30.00Italian Horror Cinema, Stefano Baschiera and Russ Hunter (eds) (2016) Edinburgh: Edinburgh University Press, 228 pp., ISBN: 9781474419680, £24.99 (trade paper)S/Murare il Mediterraneo (Un/Walling the Mediterranean). Pensieri critici e attivismo al tempo delle migrazioni ('Critical thoughts and activism in a time of migrations'), Luigi Cazzato and Filippo Silvestri (eds) (2016) Lecce: Pensa Multimedia, 256 pp., ISBN: 9788867603817, p/bk, €18.00